Pengaruh Boyband Korea sebagai Duta Merek, Kepribadian Merek, dan Gelombang Budaya Korea terhadap Minat Beli Produk Sheet Mask: Studi Kasus pada Merek Mediheal - Naomi Kusumawardani; Anggun Pesona Intan Puspita (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to determine the influence of Korean boyband as brand ambassador, brand personality, and Korean wave on purchase intention in sheet mask products from Mediheal brand, one of the beauty products from South of Korea. The sample in this research amounted to 121 women who live in Jakarta, Depok, Tangerang, and Bekasi. The sampling technique used is judgment sampling method in non probability sampling technique. Primary data used in the study were obtained through questionnaires, at the same time the secondary data were collected from previous research, journals, internet, and relevant books. This research used multiple linear regression analysis tools in examining the effect of the independent variables on the dependent variable. The result of this study shows that simultaneously the Korean boyband as brand ambassador, brand personality, and Korean wave on purchase intention to buy Mediheal sheet mask products is 51.8%, while the remaining 48.2% is influenced by variables outside of this study. Partially, only brand personality and the Korean wave have positive and significant effect on purchase interest in sheet mask products from Mediheal brand